Development of a Moisturizing Cream based on Prickly Pear Seed Oil - KLAAI, Lisa (Biopolymer Applications Journal, 2025)
In this work, we developed a moisturizer based on prickly pear seed oil, highly valuable oil for its anti-aging benefits on the skin. To achieve this, we conducted several research studies and analyses. First, we studied the raw materials: prickly pear seed oil, Shea butter, and surfactants, in order to create a stable oil-in-water emulsion. In the second part, we performed several tests and analyses: a centrifuge test, which allowed us to choose the right surfactants for a better emulsion; a pH test, which assesses the effectiveness of the cream produced. This is often considered a significant parameter in order to ensure a cream’s pH is close to that of human skin; viscosity measurement determines whether it is viscous enough to be "sticky" or easy to spread; and finally, we performed five antibacterial tests: enumeration and detection of mesophilic aerobic bacteria, enumeration of yeasts and molds, Staphylococcus aureus, detection of Pseudomonas aeruginosa, and detection of Escherichia coli. From this, we obtained our glossy, white, highly viscous moisturizer with a pleasant odor that poses no harmful effects on human skin.